UMPSA Journals secure second and third place for Best Journal Article at 15th MAPIM-KPT Awards - Fadhilah, Abdul Ghaffar (UMPSA, 2024)
PUTRAJAYA, 18 December 2024 – Journals published by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Press were awarded second and third place for Best Journal Article at the 15th Majlis Penerbitan Ilmiah Malaysia (MAPIM)-Ministry of Higher Education (MOHE) Awards 2024, held at Dewan Za’aba, Ministry of Higher Education.